Static Buckling of FML Columns in Elastic-Plastic Range. - Kołakowski, Zbigniew; Kowal-Michalska, Katarzyna (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2016)
The paper deals with the elasto-plastic buckling of thin-walled Fiber Metal Laminates short columns/profiles subjected to axial uniform compression. Structures of open and hollow (closed) cross-sections are considered build of at plate walls. Multilayered FML walls are considered as built of alternating layers of aluminum and fiber-glass composite. Three elastic-plastic theories are employed for constitutive relations description of aluminum layers i.e. fully elastic material behavior, the J2-deformation theory of plasticity and the J2 flow theory later both with Ramberg-Osgood formula application, whereas composite layers are assumed elastic within whole loading range. Some exemplary results determined with the application of own analytical-numerical method based on the Koiter's theory, in the Byskov and Hutchinson formulation are enclosed in the form of tables and plots.
Keywords: fiber metal laminates; elasto-plastic buckling; thin-walled structures; laminaty metalowo-włókniste; elastyczno-plastikowe wyboczenia; cienkościenne struktury